A study of pipe leak source location using single channel accoustic emission system - Muhammad Khairi, Ghazali (2011)
This project discusses the study of a new approach of Acoustic Emission Testing (AET) for pipeleak detection. The conventional practice of AET usually use at least two Acoustic Emission(AE) sensors to detect the leak location which is expensive. Therefore, this project was carried out to overcome this problem by using only one AE sensor to detect leak. The objective of this project is to develop an algorithm by using acoustic emission technique to detect pipe’s leak. The project design for this project is by using a test rig which is equipped by a one meter leaked galvanized iron (GI) pipe with size ¾ inch diameter, a hydraulic bench, acoustic emission sensor, acoustic emission node and acoustic emission software. The RMS value of AE wave were recorded and analyzed. An average value of RMS was determined from those four reading at each points. The result shows that the leak at pipe can be determined from the inclination or slope of the graph average vs distance. The leak is located when the slope of the graph, -0.0008 ± 0.0006. The results of the experiment prove that using one acoustic emission sensor can detect the leak location at pipeline.